RELATIONSHIP BETWEEN Socio-Economic Factors Of Beef Cattle Breeding Farmers And The Response To Artificial Insemination Technology In Pantenan Village, Panceng District, Gresik Regency - Aria, Arif; cita; Dony (UNIVERSITAS ISLAM LAMONGAN, 2024)
This study was to determine the relationship between socioeconomic factors of beef cattle breeders and the response to artificial insemination technology in Pantenan Village, Panceng District, Gresik Regency. Several socio-economic factors as variables used in this study are formal and non-formal education factors, age factors and income. The random sampling method used is by taking random samples of 34 farmers or 30% of the population of 112 farmers. As for knowing the relationship between variable X (Socio-Economic Factors) and variable Y (Farmers' Response to Artificial Insemination Technology) using the Chi-Square test. The results of the analysis show that there is no relationship between formal education factors and responses to artificial insemination technology, this is indicated by X 2 hit = 3.78 < X 2 table = 3.84, at a confidence level of 95%; but there is a relationship between the level of non-formal education and the response of farmers in implementing IB, this is shown by X 2 hit = 17.23 > X 2 table = 3.84, at a confidence level of 95%; there is a relationship between age and the response of farmers in implementing the IB program, this is shown by X 2 hit = 6.76 > X 2 table = 3.84, at a confidence level of 95%; and there is a relationship between the level income r on the response of farmers in implementing the IB program, this is shown by X 2 hit = 11.93 < X 2 table = 3.84, at a 95% confidence level.